HUBUNGAN ANTARA JENIS SEPATU DAN TINGGI HAK SEPATU DENGAN NYERI TUMIT (PLANTAR FASCIITIS) PADA PEGAWAI KANTORAN - Pradnyandari, Kadek Shinta; Nurhesti, Putu Oka Yuli; Juniartha, I Gusti Ngurah (Coping: Community of Publishing in Nursing; Vol 10 No 1 (2022): Februari 2022DO - 10.24843/coping.2022.v10.i01.p12, 2022)
Heel pain (Plantar Fasciitis) is an inflammation of the band of tissue (plantar fascia) that extends from the heel to the toes. Plantar fasciitis affects mostly active working adults. One of the factors causing plantar fasciitis is the use of shoes that do not fit properly. Previous research has shown that most plantar fasciitis is caused by wearing high heels. There is still a little research on other types of shoes such as wedges, flatshoes and loafers that can cause plantar fasciitis, so researchers want to investigate this. This study aims to determine the correlation between the type of shoes and heels with plantar fasciitis in office employees. This research was a descriptive correlative study that used a cross-sectional approach. As many as 160 respondents were obtained through simple random sampling technique. The data analysis used the Spearman Rank test. The results of this study indicate that there is a weak positive correlation between the type of shoes and the plantar fasciitis in office (?=0,05; p value=0,03; r=0,23) and there is a moderate positive correlation between high heels with plantar fasciitis in office employees (?=0,05; p value=0,18; r=0,57). ). Based on the results of the study, it is found that there is a significant correlation between shoe type and heel height with plantar fasciitis in office employees. Therefore, it is expected that office employees can choose shoes that suit their needs in order to minimize the occurrence of plantar fasciitis. This research is expected to develop knowledge in the field of ergonomics and occupational health in nursing in order to adjust the body to the choice of shoes so that it remains comfortable when working and improve quality of life.